Publications by Indian authors on erector spinae plane block: A bibliometric analysis - Tuhin Mistry; Abhijit S. Nair; Ujjwalraj Dudhedia; Sandeep Diwan (Indian Journal of Anaesthesia)
The erector spinae plane block (ESPB), first described in 2016, has gained immense popularity worldwide due to its simplicity and effectiveness in providing pain relief for various surgeries. This bibliometric analysis aims to assess the contribution of Indian authors to the body of literature on ESPB. We searched Scopus using the keywords ‘erector spinae plane block’ and ‘India’. The retrieved data were analysed using VOSviewer software. The analysis was done for co-authorship, co-occurrence, citation, bibliographic coupling and co-citation. From the 485 hits obtained after the database search, we included 262 articles for bibliometric analysis using the VOSviewer software. Co-authorship networks were identified among the All India Institute of Medical Sciences (AIIMS) in Bhubaneswar, the Postgraduate Institute of Medical Education and Research in Chandigarh and Sree Balaji Medical College in Chennai. The majority of publications originated from AIIMS, New Delhi and Bhubaneshwar. The Indian Journal of Anaesthesia published the highest number of ESPB-related articles (50), which collectively received 527 citations. This bibliometric analysis provides comprehensive details of the journals, citations, authors and institutions that have published articles on ESPB, including those authored by researchers from India. The findings may guide future research planning and collaboration using ESPB as an intervention.